Design and development of HMI software for power system health management system using C# - Lai, Kin Sen (Nanyang Technological University, 2020)
This document provides details and explanations on the final year project. The document consists of the following chapters, introduction, literature review, methodology, machine learning, problems encountered, conclusion, future work, and reflection. The introduction chapter explains the project background, motivation, project objective, scope, and organization of the report. The literature review chapter explains definitions such as predictive maintenance, internet of things, cloud and machine learning. The methodology chapter provides readers a step by step instructions to reconstruct the project for future enhancement. The machine learning chapter explains the data preparations and machine learning analysis carried out in this project. The problems encountered chapter explains the challenges faced by the student. The conclusion summarizes the main points of the project. The future work chapter is a list of recommendations to improve on the current project. Towards the end of the report, there is a reflection chapter to review the learning journey during this final year project.